General preventive effects of disqualifications of freedom from gender violence (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The present article studies the problems of deterrent effect of the privative of liberty sanctions in the area of domestic violence against women, by means of analysis the batterer deterrent effects on either repeat victimization or repeat offendingand the general preventive effects on criminal punishment, before domestic violence according to results from criminological research.
Keywords: domestic violence; prison; arrest; general prevention; deterrent.